Social Issues in Egyptian Literature An Analytic Study through Selected Novels of Abdul Halim Abdullah - Abideen, Dr. Zain ul (Acta-Islamica, 2022)
This paper sheds light upon the social role of novelist to highlight the social issues of his societythrough his literature. The study analyses the social issues in Egyptian Literaturethrough selected novels of Abdul Halim Abdullah. Theimportant social issues raised by Abdul Halim Abdullah n the selected novels are: social classifications, late marriages in older age, raising children, doubt and lack of trust in spouse, cheating and unfaithfulness, love, and poverty.